Climate change : learning about what is happening with the weather in central Australia - Mooney, Meg; Walsh, Fiona; Hills, Ro; Davies, Jocelyn; Sparrow, Ashley D.; Rangers, Ltyentye Apurte (2014)
This resource was written to provide Indigenous communities and others with an understanding about climate change. It also aims to encourage people in Indigenous communities to talk about climate change, and what will help their communities deal with these changes in the weather.
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; openalex:import; openalex:yes; ⛔ No DOI found